(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
Osteoporosis is a systemic skeletal disease characterized by reduced bone mineral density and a deterioration of bone microarchitecture, resulting in an increased susceptibility to fractures. This condition is highly prevalent in postmenopausal women and the elderly. The etiology is multifactorial, encompassing hormonal, genetic, nutritional, and environmental factors. Early diagnosis and intervention are critical in preventing fractures and improving quality of life. This paper explores the etiology, clinical presentation, and diagnostic approaches to osteoporosis, with a focus on evidence-based criteria and guidelines for clinical practice.